Navigating modern dating: the impact of gender stereotypes and perceived social roles on individuals' perceptions of others' online dating profiles - Chan, Jen-Le Jemima (Nanyang Technological University, 2024)
Dating applications have been seeing a rapid rise in popularity over the last few years, presenting a new way to meet potential partners online. While there is extensive research on gender stereotypes and social roles in general, studies on how these intersect with the digital space is still a relatively emerging topic of research, and there are even fewer studies that focus specifically on a Singaporean or Asian context. This research paper aims to close this gap and provide further insight into how gender stereotypes and social roles intersect and affect the way Singapore young adults evaluate others on dating apps. In our study, a 2x2 between-subject factorial experiment (N = 220) was conducted to investigate the interaction effects of gender stereotypes and perceived social roles on different measures of romantic attraction in the context of a dating app profile. Our results showed some patterns in these interaction effects, and this paper further discusses the reasons for these and broader findings. They can then be used to evaluate whether the above social constructs are changing with the 21st century, and further deepen our understanding of how individuals find others romantically attractive in the digital space.